Editorial (diségno, 2022)
Since 2018, the Archives Commission of the Unione Italiana per il Disegno (UID), coordinated by Caterina Palestini, has invested heavily in the project entitled Il Disegno negli Archivi di Architettura (Drawing in the Archives of Architecture) with the aim of communicating, through an examination of the research carried out by teachers and researchers in the disciplinary field, the contribution that graphic analysis and representation, both traditional and digital, can make on the subject of the Archives of Architecture and Civil Engineering. [read more]